IMPLIKASI IKLIM ORGANISASI, MUTASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI BKPSDM KABUPATEN SUBANG - Wawan Hermawan; Sedarmayanti Sedarmayanti; Edah Jubaedah; Mulyaningsih Mulyaningsih (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2020)
Changes in organizational climate and employee mutation as a consequence of changes in organizational structure are the interesting things for an object of research. This research is directed to explaine the influence of organizational climate and mutation through job satisfaction on employee performance in BKPSDM Subang Regency. This research uses a quantitative approach. Collecting data through distributing questionnaires to employees and interviews. Data were analyzed using Structural Equation Modeling. Â The analysis shows that: The influence of organizational climate on job satisfaction is categorized as weak but significant. The influence of mutation on job satisfaction is categorized as weak and insignificant. The influence of organizational climate on employee performance is categorized weak and significant. The effect of mutations on employee performance is categorized weak and it is not significant. The effect of job satisfaction on employee performance is categorized weak but significant. The influence of organizational climate and mutation on job satisfaction is categorized moderate and significant. The influence of organizational climate, mutation and job satisfaction on employee performance categorized as moderate and significant. The efforts that can be made to improve employee performance in BKPSDM Subang Regency are by giving fair rewards to employee performance, carrying out mutations in a planned and periodic manner, and improving communication between work units so as to create synergies to achieve performance targets.